2016
DOI: 10.1016/j.jchromb.2015.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic analysis of the effects of fatty acids and glycation on binding by probes for Sudlow sites I and II to human serum albumin

Abstract: The primary endogenous ligands of human serum albumin (HSA) are non-esterified fatty acids, with 0.1–2 moles of fatty acids normally being bound to HSA. In type II diabetes, fatty acid levels in serum are often elevated, and the presence of high glucose results in an increase in the non-enzymatic glycation of HSA. High-performance affinity chromatography (HPAC) was used to examine the combined effects of glycation and the presence of long chain fatty acids on the binding of HSA with R-warfarin and L-tryptophan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In site II, the docking scores of polymethoxy flavonoids were higher than at site I. This phenomenon was consistent with the tendency of site I to bind bulky heterocyclic anionic compounds and site II to aromatic carboxylates [ 57 ]. Moreover, the effect of a hydroxyl on glycosyl was found to be less than that of a hydroxyl on the parent nucleus, perhaps because of the large area of steric hindrance [ 58 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…In site II, the docking scores of polymethoxy flavonoids were higher than at site I. This phenomenon was consistent with the tendency of site I to bind bulky heterocyclic anionic compounds and site II to aromatic carboxylates [ 57 ]. Moreover, the effect of a hydroxyl on glycosyl was found to be less than that of a hydroxyl on the parent nucleus, perhaps because of the large area of steric hindrance [ 58 ].…”
Section: Resultssupporting
confidence: 75%
“…Working factors of pH and temperature influenced the activity of HSA, time of incubation influenced the binding degree of binders, eluting steps removed the disturbance of unbound compounds, and dissolution reagent was necessary for the dissociation of HSA-drug complexes. Optimum conditions in the study were established by referring to related studies [ 56 , 57 , 58 ] which performed single factor experiments in previous work. This study was performed at 37 °C (physiological temperature) with pH 7.4 (the plasma condition) to provide optimal reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most common drug binding sites of albumin are located in the hydrophobic cavities of subdomain IIA and IIIA, known as Sudlow's sites I and II, respectively (53). Non-esterified medium-and long-chain fatty acids, such as myristic and palmitic acid, can bind to seven sites on HSA, three of which are located on Sudlow's drug binding sites I and II (54,55). In particular, the albumin region from residues 377-582, including part of domain II and the entire domain III was found to be the primary binding site for long chain fatty acids (56) and, more precisely, the key roles of R410 (Sudlow's site II) and K525 (domain IIIB) for fatty acid binding has been reported (57).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, heparin provokes the release of lipolytic enzymes [44], leading to hydrolysis of triglycerides and release of free fatty acid and increasing their plasma concentrations. It has been shown that free fatty acids displace drugs and ligands (also for IS, IAA and Trp) from their protein binding sites [45,46] and that Trp increases displacement of IS and IAA [47]. IS, IAA and Trp primarily bind to Sudlow site II on albumin, with IS having the highest affinity [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%